A qualitative study of Argentine small and medium enterprises: Factors driving social responsibility. Issue 1 (30th June 2019) - Massoud, Jacob A.; Daily, Bonnie F.; Willi, Alberto
Abstract: Small and medium‐sized enterprise (SMEs) social responsibility has recently begun to gain greater importance in Argentina due to a variety of contextual factors. The main area of inquiry investigated in this study was the motivation for adopting social responsibility initiatives at Argentine SMEs. Exploratory, qualitative methods were employed to evaluate social responsibility initiatives at six firms across several industries. Semistructured interviews served as the primary source of data. Data were analyzed and interpreted using open coding to develop categories and themes. Results indicate that the chief motivation for SMEs to engage in social responsibility rests primarily in the values of company owners or managers. Additional external factors such as labor demands and the economy also influence a firm's choice of corporate social responsibility (CSR) initiative. The findings also provide the broader business community with several lessons that could be applied to enhance CSR efforts. Similar to prior research, it was found that both internal and external factors influence the adoption of CSR by SMEs, demonstrating strong support for the roles of an owner's values and the community as key drivers.